2001
DOI: 10.2310/6650.2001.33969
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of P-Glycoprotein in Mouse Intestine, Liver, and Kidney

Abstract: We conclude that Pgp is expressed in a tissue-specific and developmentally regulated fashion and speculate that developmental modulation of intestine-Pgp expression may affect the oral bioavailability of Pgp substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
2
22
3
Order By: Relevance
“…In earlier studies, developmental changes in MDR1/mdr1 protein levels have been examined in mice, rats, or humans using the monoclonal antibody C219. The findings of reduced C219 immunoreactivity from those studies have suggested decreased P-gp in the brain, liver, and kidney in fetal or immature animals compared with adults (Schuetz et al, 1995;Matsuoka et al, 1999;Mahmood et al, 2001;Watchko et al, 2001). In support of the protein data, two recent studies have determined, by semiquantitative PCR, that mdr1a expression in the mouse brain and mdr1a and mdr1b expression in the rat brain, liver, and kidney increased with maturation (Tsai et al, 2002;Rosati et al, 2003).…”
supporting
confidence: 54%
“…In earlier studies, developmental changes in MDR1/mdr1 protein levels have been examined in mice, rats, or humans using the monoclonal antibody C219. The findings of reduced C219 immunoreactivity from those studies have suggested decreased P-gp in the brain, liver, and kidney in fetal or immature animals compared with adults (Schuetz et al, 1995;Matsuoka et al, 1999;Mahmood et al, 2001;Watchko et al, 2001). In support of the protein data, two recent studies have determined, by semiquantitative PCR, that mdr1a expression in the mouse brain and mdr1a and mdr1b expression in the rat brain, liver, and kidney increased with maturation (Tsai et al, 2002;Rosati et al, 2003).…”
supporting
confidence: 54%
“…Levels of mdr1b on the other hand, were all significantly different from adult, which the authors concluded indicates a steady, more gradual rise in expression. Contrary to these studies, Mahmood et al found no evidence for postnatal changes in renal P-gp (13). They used Western blotting to quantitate levels of protein and concluded that at all age groups, protein levels were 96 袭 15% of adult levels.…”
Section: Discussionmentioning
confidence: 89%
“…Dutt (13,21,22). We used FVB mice in our study, similar to Mahmood et al The use of different techniques could also account for some differences seen.…”
Section: Discussionmentioning
confidence: 95%
“…Preweanling rats are shown to have relatively high GI absorption rates (Hoffman, 1982;Naylor and Harrison, 1995). Pglycoprotein, which may play a role as an efflux transporter of pyrethroids (Bain and LeBlanc, 1996;Buss et al, 2002) has been found to be deficient in young mice (Mahmood et al, 2001). Extensive absorption and/or decreased efflux from the GI tract of young animals could contribute to the higher internal exposure and toxicity of DLM.…”
Section: Age-dependent Toxic Signs Following Dlm Administrationmentioning
confidence: 99%